Evaluasi Kualitas Materi Dalam Buku Siswa Matematika Sd Kelas V Edisi Revisi 2018 Berdasarkan Kriteria Bell - Fazrin, Mutiara; Irawati, Riana; Isrokatun, Isrokatun (Jurnal Pena Ilmiah, 2021)
Teaching materials, one of which is books, are essential components in the learning process. Conceptual errors of a textbook will result in errors in students' understanding. For this reason, the evaluation of the 2018 Revised Edition of the Class V Elementary School Mathematics Student Book using the bell's criteria aimed to assess the quality of the material contained in the book. The research method used in this study is a qualitative method with a content analysis design. The object of this research is the document of mathematics students' books and students who use the book. The instruments used are interview guidelines and evaluation sheets. The study result, the quality of the 2018 Revised Edition of the Class V Elementary School Mathematics Student Book based on the bell's criteria has good quality. Because almost all of the material presented has met the bell's criteria.